Multi-sector framework for benchmarking in facilities management. Issue 4 (2nd May 2017) - Adewunmi, Yewande Adetoro; Iyagba, Reuben; Omirin, Modupe
Abstract : Purpose: Benchmarking in FM practice although understood and applied globally, little is known about the practice in Nigeria. The purpose of this paper is to develop a framework to guide the use of benchmarking. Design/methodology/approach: The research adopts a cross-sectional survey design. Data were collected using self-administered questionnaires on FM organizations in Lagos metropolis, Abuja and Port Harcourt. The results of the survey were supplemented with interviews with FM unit heads in the study areas. The framework was validated using a focus group discussion with ten FM industry experts. Findings: A framework which serves as a guide for the use of best practice benchmarking was developed. It showed that there is a relationship between best practice benchmarking and location. Research limitations/implications: The evaluation of the framework was limited by the number of participants involved and being that it has not been put to use. Originality/value: This study develops a multi-sector framework to guide the use of best practice benchmarking in facilities management (FM). The framework explains the relationship between organizational characteristics and best practice benchmarking. In addition, there are limited empirical benchmarking frameworks in FM literature.